Predicting medication adherence in older Hispanic patients with type 2 diabetes. (1st May 2018) - Caballero, Joshua; Ownby, Raymond L.; Jacobs, Robin J.; Pandya, Naushira; Hardigan, Patrick C.; Ricabal, Lazara C.
Abstract : Purpose: Potential cognitive and demographic correlates of medication nonadherence in older Hispanic adults with type 2 diabetes were investigated. Methods: Forty community-dwelling participants 65 years of age or older were recruited. Executive control function (ECF) was assessed using the executive clock drawing task (CLOX 1) test and the 25-item Executive Interview. Self-reported medication adherence was measured on a visual analog scale (VAS); measures of glycemic control included glycosylated hemoglobin (HbA1c ) concentration. The primary objective was to determine if ECF performance correlated with medication adherence or glycemic control. Results: Participants' mean ± S.D. age was 74.95 ± 7.07 years, and 73% ( n = 29) were female. Lower VAS scores correlated with worse CLOX 1 performance ( r = 0.38, p = 0.02) and worse HbA1c status ( r = −0.42, p = 0.007). Linear regression modeling indicated significant associations between VAS scores and both CLOX 1 results (beta coefficient [β] = 0.41, p = 0.01) and educational level (β = 0.345, p = 0.03). Receiver operating characteristic analysis of CLOX 1 scores (scoring range, 0–15; lower scores indicate greater impairment) showed that a highly sensitive cutoff score for predicting adherence of <90% would be 7, but a cutoff of 10 would provide more specificity. Conclusion: Results of an evaluation of a small sample of Hispanic older adults with type 2 diabetes demonstrated a relationship between ECF, as measured by the CLOX 1 instrument, and self-reported medication adherence.